Diazoxide use for neonatal hyperinsulinaemic hypoglycaemia in a low-resource setting: A Case Report - Adekoya AO; Adekanye TE; Abolurin OO; Adebawojo OO; Ajayi FG; Ajibola ED (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
The management of neonatal hyperinsulinaemic hypoglycaemia remains a major challenge in hospitalized newborns globally. Diazoxide is one of the recommended therapeutic options. We report a late preterm, male infant of a diabetic mother who suffered severe perinatal asphyxia and had persistent hypoglycaemia requiring progressively increasing intravenous glucose concentrations to as high as 12.5 mg/kg/minute along with intravenous hydrocortisone administration. A critical sample revealed inappropriately high serum insulin, inappropriately low serum cortisol and growth hormone responses. Urinalysis was negative for ketones. With the persistence of hypoglycaemia, oral diazoxide at 5 mg/kg/day with oral hydrochlorothiazide was administered. The infant was diazoxide-responsive with complete resolution of hypoglycaemia. Diazoxide therapy was discontinued after 14 days and he was discharged after one month of admission. This report emphasizes the importance of diazoxide in the management of neonatal transient hyperinsulinaemic hypoglycaemia. The availability and cost of diazoxide, as well as the endocrine and metabolic tests, are major concerns in resource-poor settings.